DOKUMEN NON-ARAB TENTANG BERITA KERASULAN MUHAMMAD DAN AWAL ISLAM - Hasyim Asyari (Humaniora, 2006)
In the era of the beginning of Islam, Arabia was situated among great imperial countries which are intellectually and culturally more developed as a result of development of religious life especially Jews and Christianity. So, it is not surprising if lots of written artifacts concerning with the emergence of new religion and its Prophet, Muhammad, are found in Arabia. The documents are of course very meaningful in the historiography of Islamic history and tradition on its formative period, since the sources proportionally can also be completed by obtaining information from documents of non-Arabic Islamic chronicles. The non-Arabic contemporary sources of this primitive Islam may offer different kinds of account to study on how Islam has developed to the present form, since this kind of testimony is a comparative historical entity rather than a conventional one. The non-Arabic sources concerning Islam imply non-Islamic points of view, nevertheless they are certainly of valuable meaning in the study of any history.